The Impact of High Dose Ozone Therapy on Hematological and Biochemical Profiles : An Observational Study - Digambiro, Reza Aditya; Parwanto, Edy; Lestari, Indah Widya; Chendrasari, Julian; Setyaningrum, Dyah Ayu Woro; Ilona, Florinda (The Avicenna Medical Journal, 2024)
Background: Ozone therapy, namely High Dose Ozone Therapy (HDO), has become a versatile medical treatment in several clinical settings. Although it is becoming more well acknowledged, there is still a lack of extensive evidence about the impact of this on hematological and biochemical indicators. This study seeks to address this void by examining the consequences of this phenomenon in a clinical environment.Method: An observational study was done, which followed a structured approach, comprising a total of 100 patients who were selected from the SMC Clinic. Hematological and biochemical indices were evaluated before and after ozone therapy sessions to analyze blood parameters. Two blood samples were obtained at two specific time points: prior to the commencement of the ozone therapy (T0) and after the therapy was finished (T1).Results: Substantial alterations were noted in both hematological and biochemical parameters after the therapy. The hematological changes observed in this study showed a substantial rise in the red blood cell count (p=0.009), hemoglobin levels (p=0.004), and hematocrit (p=0.039), along with a decrease in erythrocyte sedimentation rate (ESR) (p=0.020). Notable biochemical changes were observed, including significant modifications in total plasma protein (TPP) (p=0.008) and lactate levels (p=0.001). Furthermore, there was a noteworthy decrease (p<0.05) in the levels of malondialdehyde (MDA), which is a marker for oxidative stress.Conclusion: HDO exerts a regulatory influence on crucial hematological, biochemical, and oxidative stress factors. These findings indicate that HDO may have therapeutic benefits for treating chronic disorders and cancer. It can improve blood parameters and reduce oxidative stress. The decrease in markers of oxidative stress, such as MDA, suggests a potential reduction in the likelihood of problems associated with oxidative damage in chronic diseases. Nevertheless, additional research is required to validate these findings, investigate their wider therapeutic implications, and comprehend the long-term consequences and safety of HDO therapy.